Effect of Rehydration Temperature of Active Dried Yeast on Wine Production and quality - Tracey, R.P.; Simpson, Estelle (South African Journal of Enology and Viticulture, 2017)
The effect of rehydration temperature on 11 active dried yeast preparations was studied. Rehydration temperatures varied from 20°C to 47°C. Fermentation rate, cell viability and leached solids were determined at each temperature. The effect of yeast rehydration temperature on wine quality of four wine cultivars was also determined. Results showed that yeast strains differ in their optimum rehydration temperatures and that rehydration temperatures between 35°C and 39°C will yield maximum fermentation rates. The optimum rehydration temperature for cell viability was on average higher than that for the maximum fermentation rate. Differences in wine quality were found, but no specific conclusion could be made with regard to a specific yeast strain.